2017
DOI: 10.2136/sssaj2016.08.0249
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of Nitrous Oxide Emission in Fertilized and Unfertilized Perennial Grasses

Abstract: Core Ideas We studied hotspots of nitrous oxide emission from perennial grasses on wet soil. Hotspots occurred in a limited range of soil moisture and temperature conditions. Hotspots recurred more frequently at specific places over a three year period. Hotspots of nitrous oxide (N2O) emission are thought to contribute substantially to annual emissions from agricultural soils. We observed N2O fluxes from fertilized and unfertilized C3 and C4 perennial grasses on a wet silt loam soil in New York, United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Especially in Villa Grove site, hotspots that covered only 12% of the area contributed more than half of the field's N2O emission. This level of disproportion with N2O hotspots has been observed in grazed grasslands, largely due to focused disposition of manure, which could be analogous to spatially heterogenous application of N fertilizers in the row crop systems (Cowan et al, 2015;Mason et al, 2017). A past study on a corn-soybean rotation system similar to Bondville and Pesotum sites reported that N2O hotspots (21% area) contributed 36% of the field-wide emission, relatively less disproportionate than our observations (Turner et al, 2016).…”
Section: Contributions Of Co2 and N2o Hotspots To Field-wide Fluxessupporting
confidence: 53%
See 1 more Smart Citation
“…Especially in Villa Grove site, hotspots that covered only 12% of the area contributed more than half of the field's N2O emission. This level of disproportion with N2O hotspots has been observed in grazed grasslands, largely due to focused disposition of manure, which could be analogous to spatially heterogenous application of N fertilizers in the row crop systems (Cowan et al, 2015;Mason et al, 2017). A past study on a corn-soybean rotation system similar to Bondville and Pesotum sites reported that N2O hotspots (21% area) contributed 36% of the field-wide emission, relatively less disproportionate than our observations (Turner et al, 2016).…”
Section: Contributions Of Co2 and N2o Hotspots To Field-wide Fluxessupporting
confidence: 53%
“…For this goal, multiple large-scale, high-resolution campaigns have been conducted, despite their tremendous costs and labor. For example, field-scale soil GHG flux studies have identified soil N level (Cowan et al, 2015), soil moisture (Charteris et al, 2021;Mason et al, 2017), and topography (Ashiq et al, 2021;Turner et al, 2016) as important predictors of N2O spatial patterns and hotspots. The spatial resolutions of these studies ranged as low as four measurement points ha -1 (Turner et al, 2016) to 55 points ha -1 (Charteris et al, 2021), although such high spatial resolution measurement was done only at a single time point during a season.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical approaches were deployed to identify areas that may have disproportionately contributed to the overall landscape GHG fluxes (e.g., van Kessel et al, 1993;Mason et al, 2017). We defined the threshold for hot spots using the sum of the median (M) flux and the interquartile (Q3-Q1) flux range (Eq.…”
Section: Identification Of Ghg 'Hot' and 'Cold' Spots From Predicted ...mentioning
confidence: 99%
“…Agricultural N 2 O emissions can increase exponentially with increasing fertilizer application rates (Millar et al, 2018;Shcherbak et al, 2014), highlighting the need for site-specific research over linear emission factors such as those used in the Intergovernmental Panel for Climate Change's (IPCC) methodologies (IPCC, 2006). Accurate measurements of N 2 O emissions are difficult to make because of the high degree of spatial and temporal variability in emissions, or "hot spots" and "hot moments" (Mason et al, 2017;McClain et al, 2003;Molodovskaya et al, 2012;Nicolini et al, 2013). Static chambers (SC) have been used for decades to measure emissions of N 2 O from soils; more recently the use of automated multichamber systems has enabled a high degree of temporal coverage relative to manual chambers, but coverage of spatial heterogeneity can still be inadequate (Barton et al, 2015;Butterbach-Bahl et al, 2013;Loescher et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate measurements of N 2 O emissions are difficult to make because of the high degree of spatial and temporal variability in emissions, or "hot spots" and "hot moments" (Mason et al, 2017;McClain et al, 2003;Molodovskaya et al, 2012;Nicolini et al, 2013). Static chambers (SC) have been used for decades to measure emissions of N 2 O from soils; more recently the use of automated multichamber systems has enabled a high degree of temporal coverage relative to manual chambers, but coverage of spatial heterogeneity can still be inadequate (Barton et al, 2015;Butterbach-Bahl et al, 2013;Loescher et al, 2006).…”
Section: Introductionmentioning
confidence: 99%